The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1159/000327898
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Exercise Training for the Short-Term Treatment of Generalized Anxiety Disorder: A Randomized Controlled Trial

Abstract: Background: Exercise training may be especially helpful for patients with generalized anxiety disorder (GAD). We conducted a randomized controlled trial to quantify the effects of 6 weeks of resistance (RET) or aerobic exercise training (AET) on remission and worry symptoms among sedentary patients with GAD. Methods: Thirty sedentary women aged 18–37 years, diagnosed by clinicians blinded to treatment allocation with a primary DSM-IV diagnosis of GAD and not engaged in any treatment other than pharmacotherapy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(112 citation statements)
references
References 49 publications
3
104
0
1
Order By: Relevance
“…The factors that may be related to this fact are numerous, such as: severity of symptoms of anxiety, duration of intervention, volume and intensity of exercise and even the fact that the exercise is aerobic or strength. Studies that had their focus on samples with anxiety disorders [13][14][15][16][17][18][19][20][21][22] also showed mixed results. Of these, three studies [20][21][22] analyzed the efficacy of aerobic exercise compared to non-aerobic exercise in reducing anxiety disorders, the first study [20] showed a significant reduction of anxiety disorders for both groups, aerobic and non-aerobic compared the baseline, but with no difference between the groups, with the following exercise protocol: (3x week, 60min, for 8 weeks) aerobic 70% of VO2max (high intensity) and strength (low intensity).…”
Section: Methodological Differencesmentioning
confidence: 99%
See 3 more Smart Citations
“…The factors that may be related to this fact are numerous, such as: severity of symptoms of anxiety, duration of intervention, volume and intensity of exercise and even the fact that the exercise is aerobic or strength. Studies that had their focus on samples with anxiety disorders [13][14][15][16][17][18][19][20][21][22] also showed mixed results. Of these, three studies [20][21][22] analyzed the efficacy of aerobic exercise compared to non-aerobic exercise in reducing anxiety disorders, the first study [20] showed a significant reduction of anxiety disorders for both groups, aerobic and non-aerobic compared the baseline, but with no difference between the groups, with the following exercise protocol: (3x week, 60min, for 8 weeks) aerobic 70% of VO2max (high intensity) and strength (low intensity).…”
Section: Methodological Differencesmentioning
confidence: 99%
“…Studies that had their focus on samples with anxiety disorders [13][14][15][16][17][18][19][20][21][22] also showed mixed results. Of these, three studies [20][21][22] analyzed the efficacy of aerobic exercise compared to non-aerobic exercise in reducing anxiety disorders, the first study [20] showed a significant reduction of anxiety disorders for both groups, aerobic and non-aerobic compared the baseline, but with no difference between the groups, with the following exercise protocol: (3x week, 60min, for 8 weeks) aerobic 70% of VO2max (high intensity) and strength (low intensity). The second study [21] used the aerobic exercise (TAE), strength (TRE) and control (CG), one for each group and assessed the effect of these exercises in remission symptoms in patients with generalized anxiety disorder, finding reduction 60, 40 and 30% respectively for (TRE), (TAE) and (GC), although a protocol for short-term, low-intensity, aerobic with (2x week, 46min, for 6 weeks) and exercise with the same methodology, but with intensity 50-75% 1RM, 3 exercises with 7x10 repetitions, were effective in remission.…”
Section: Methodological Differencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Herring et al (2012) found that women who were suffering from anxiety disorders, or were being treated with antidepressant medications have reduced significantly the worry symptoms compared to the control group, after participating in six weeks of aerobic and resistance training. Merom et al (2008) found that patients diagnosed with panic disorder, social phobia, and generalized anxiety disorder have experienced a significant reduction in anxiety after complementing a home-based walking program.…”
Section: / Corresponding Author: Mohamed Aziz Riahi Selection and Peementioning
confidence: 94%